#TITLE_ALTERNATIVE# - HASBULLAH (NIM 10103010), ISMAIL
An f-coloring of a simple graph G = (V,E) is to color each edge in G so that, each color appears at each vertex v at most f(v) times where f : V → ℵ. Since f-coloring where f(v) = 1 for each vertex v ∈ V is NP-complete problem, then in general, f-coloring is NP-complete problem. Therefore, it is very unlikely that there exists an exact algorithm which solves the edge-coloring problem in polynomial time. This final project gives efficient algorithms to find edge-coloring and f-coloring for various classes of graphs such as wheel graphs, fan graphs and graphs with particular degeneracy, aboricity, and unicyclic index . Then, for other classes of graphs, we used heuristic algorithm.